A tutela penal diante da homofobia e o PLC 122/2006 : sobre a legitimidade da demanda político-criminal do movimento LGBT - Masiero, Clara Moura (2013)
This dissertation, developed within the research line entitled Violence, crime and public safety of the Postgraduate Program in Criminal Sciences of the Pontifical Catholic University of Rio Grande do Sul, focuses on the issue of social movemente of Lesbian, Gay, Bisexual, Transsexual and Transgender (LGBT) claim for turning homophobia as a crime and also on the political-criminal strategy to supply this demand. The LGBT movement plays the lead role in the field of struggles around sexuality and homophobia. This movement, supported academically by Queer studies, in the face of the empirical problem represented by the homophobic phenomenon, has as one of its main claims turn as a crime homophobic behavior, walking similar path of the movements of blacks and women. Therefore, there is a controversial Bill (PLC 122/2006) pending in the Brazilian National Congress, which aims to define "crimes resulting from discrimination or prejudice of gender, sex, sexual orientation and gender identity" and that, supposedly, meets the political-criminal claim of the movement. Within this framework, this paper aims to assess the legitimacy of the penal protection of homophobia and to propose what would be the most appropriate regulatory strategy for this purpose, within a critical and minimalist criminal Law view. For it, the research is divided into three parts: first, there is the revelation of the problem (heterosexist culture and homophobic phenomenon) and its rupture propose (by Queer theory); in the second part, is presented the LGBT movement and its political performance; and in the third, there is the debate around the issue of criminal protection of homophobia and the legal instrument to be chosen, when the more advanced Bill (in terms of legislative process) under discussion in Congress is evaluated. We conclude that, with a criminological view it is possible to think on the legitimacy of turning the homofobia as crime to assist in preventing and facing the violence that surrounds it, within a critical and rational criminal policy. Which should, however, discuss the strategy for it, coming to the conclusion that the creation of new crimes is unnecessary: it s sufficient just including the name homophobic crimes to some articles of the Criminal Code when motivated by homophobia, either as an aggravating factor, penalty increase cause or qualifying.